Effects of Exercise, Rehabilitation, and Nutritional Approaches on Body Composition and Bone Density in People with Multiple Sclerosis: A Systematic Review and Meta-Analysis - Natascia Rinaldo; Alba Pasini; Sofia Straudi; Giovanni Piva; Anna Crepaldi; Andrea Baroni; Lorenzo Caruso; Fabio Manfredini; Nicola Lamberti (Journal of Functional Morphology and Kinesiology, 2023)
People with multiple sclerosis (pwMS) are affected by a wide range of disabilities, including a decrease in bone mineral density (BMD) and a worsening of body composition (BC), which negatively impact their quality of life quality. This study aims to analyze the effects of nonpharmacological interventions—in particular, physical activity, nutritional approaches, and rehabilitation—on BC and BMD in pwMS. This systematic review and meta-analysis was performed following the updated version of the PRISMA guidelines. In July 2022, five databases (MEDLINE, Embase, The Cochrane Library, Google Scholar, Web of Science) and gray literature were screened. Relevant articles published between 1 January 1990 and 1 September 2022 in any language were included. Outcomes of interest were anthropometric, BC measures, and BMD. The RoB 2.0 tool was used to assess the risk of bias. After duplicates elimination, 1120 records were screened, and 36 studies were included. A total of 25 articles were focused on physical activity and rehabilitation, 10 on nutrition, and 1 on multimodal intervention. One-third of the studies were judged to be at high risk of bias. The meta-analysis showed a high degree of heterogeneity due to the high variability in disease severity and intervention duration, intensity, frequency, and type. In general, no intervention showed consistent positive effects on BC. However, the most promising interventions seemed to be high-intensity training and ketogenic diets. Only a few studies considered BMD, and the results are inconsistent. Nevertheless, more studies are needed in order to confirm these results.